Does Ownership Matter for Medical System Performance? Evidence From a Natural Experiment in Suqian, China. (July 2020) - Liu, Gordon G.; Shi, Julie; Wang, Xiaoqian; Yang, Hanmo; Zhu, Hengpeng
There has long been a major policy debate on the role of hospital ownership (private vs public) in medical system performance. China's health care delivery system is mainly a public system. In 2000, a full privatization reform was implemented in the city of Suqian, offering a unique opportunity to assess possible effects of private delivery based on a major external shock to the existing system. Compared with all other cities in Jiangsu province since 2003, Suqian did not experience any greater increase either in total outpatient or inpatient expenditures. In the meantime, Suqian performed equally well as other cities in terms of changes in number of inpatient admissions and average inpatient days, and even better for mortality rate in emergency rooms. This study concludes that under appropriate public financing, private delivery can serve the public demand at least equally well as public providers in terms of cost inflations and utilizations.